The importance of balance between flexibility and neuronal stability in memory formation - Calafate, Sara Cesariny (2021)
The neurobiological mechanisms behind memory formation remain unknown. Synapses are essential neuronal sub-compartments for the transmission of information within neuronal networks. Hebbian and homeostatic plasticity mechanisms, are two types of processes that play a role on synaptic modifications during the formation of memories. The interaction between these types of plasticity controls the balance between neuronal flexibility and stability to keep neuronal activity within a physiological window. Thus, it is important to better understand these mechanisms and identify the basic units of this system as they may be involved in the onset of neurological disorders. Here, I shed light on the impact of these mechanisms in the early phase of Alzheimer’s disease.